Blockade of Toll-Like Receptor 4 Attenuates Erectile Dysfunction in Diabetic Rats. Issue 9 (23rd August 2018) - Nunes, Kenia Pedrosa; de Oliveira, Amanda Almeida; Szasz, Theodora; Biancardi, Vinicia Campana; Webb, R. Clinton
Abstract: Introduction: While increased toll-like receptor (TLR)4 activity may contribute to the pathophysiology of vascular diseases, the molecular mechanisms disrupted by this receptor in the vasculature are still poorly understood. Additionally, it is unknown if TLR4 mediates erectile dysfunction (ED) during diabetes. Aim: To investigate whether pharmacological blockade of TLR4 affects erectile function in a murine model of diabetes. Methods: Sprague Dawley rats (Charles River Laboratory, Wilmington, MA, USA) received a single streptozotocin injection (65 mg/kg, 28 days) and were treated with an anti-TLR4 antibody (1 μg/d, intraperitoneally) for the last 14 days of the treatment. Additionally, cavernosal strips were acutely incubated for 30 minutes with CLI-095 (10 −5 mol/L), a TLR4 inhibitor. Functional studies, Western blotting, erectile function, immunohistochemistry, and biochemical analyses were performed. Main Outcome Measures: Oxidative stress, cyclic guanosine monophosphate (cGMP) levels, and functional studies were evaluated in treated and nontreated cavernosal strips from control and diabetic animals. Additionally, in vivo erectile function was assessed. Results: Enhanced TLR4 expression was observed in corpus cavernosum from diabetic rats compared with control animals. Long-term blockade of TLR4 slightly improved diabetes–induced ED in rats due to attenuation of oxidative stress and increased cGMP levels in penile tissue, which ameliorated cavernosal relaxation. Functional experiments revealed that acute or chronic inhibition of TLR4 decreased hypercontractility in response to phenylephrine and improved nitrergic relaxation in corpus cavernosum from diabetic rats. Clinical Implications: TLR4 blockade may be a novel therapeutic strategy to assist in ED management. Strengths & Limitations: The strength of this article stems from the fact that we showed that TLR4 blockade partly improves erectile function in vivo in diabetic rats. Its limitations mainly include that messenger RNA analysis for the nitric oxide/cGMP pathway were not performed. Conclusion: In summary, TLR4 participates in the mechanisms of diabetes-associated ED and blockade of this receptor positively affects penile vascular function.